Phages rarely encode antibiotic resistance genes: a cautionary tale for virome analyses - Enault, François; Briet, Arnaud; Bouteille, Léa; Roux, Simon; Sullivan, Matthew B; Petit, Marie-Agnès (The ISME Journal, 2017)
Antibiotic resistance genes (ARGs) are pervasive in gut microbiota, but it remains unclear how often ARGs are transferred, particularly to pathogens. Traditionally, ARG spread is attributed to horizontal transfer mediated either by DNA transformation, bacterial conjugation or generalized transduction. However, recent viral metagenome (virome) analyses suggest that ARGs are frequently carried by phages, which is inconsistent with the traditional view that phage genomes rarely encode ARGs. Here we used exploratory and conservative bioinformatic strategies found in the literature to detect ARGs in phage genomes, and experimentally assessed a subset of ARG predicted using exploratory thresholds. ARG abundances in 1181 phage genomes were vastly overestimated using exploratory thresholds (421 predicted vs 2 known), due to low similarities and matches to protein unrelated to antibiotic resistance. Consistent with this, four ARGs predicted using exploratory thresholds were experimentally evaluated and failed to confer antibiotic resistance in Escherichia coli . Reanalysis of available human- or mouse-associated viromes for ARGs and their genomic context suggested that bona fide ARG attributed to phages in viromes were previously overestimated. These findings provide guidance for documentation of ARG in viromes, and reassert that ARGs are rarely encoded in phages.